GANGGUAN PSIKOGENIK LATAH GARY ISKAK: KAJIAN PSIKOLINGUISTIK - Nuril Phasa, Hidayah (MIMESIS, 2022)
This research is motivated by the stigma of talkativeness suffered by women, people with low education, and belonging to the lower economic class category. The research entitled "Psychogenic Disorder of Talkative Gary Iskak (Psycholinguistic Study)" aims to describe the talkative and the background of talkative sufferers towards artist Gary Iskak. The theory used in this research is the talkative theory of  Abdul Chaer and Soenjono Darjowidjodjo with a psycholinguistic approach. The data collection method used is the referential method with the note-taking technique. In contrast, the data analysis method is the referential method with the determining determinants or the PUP technique. The results found in this study are that there are four general reaction types: Ekolalia, Ekopraxia, Auto Ekolalia, and Automatic Obedience. Then the two types of talkative reactions that are not included in the four categories are a mixture of Ekolalia and Ekopraxia talkative and the impact of voice talk. In addition to the type of talkativeness, it was also found that the factors causing the talkativeness experienced by Gary Iskak when he was in several events found four causes of talkativeness. Among the four, the most frequent cause of talkativeness is being surprised by other people's movements.